Conservation of an Endangered Medicinal Tree Species Taxus wallichian through Callus Induction and Shoot Regeneration (Plant Tissue Culture and Biotechnology, 2020)
Abstract Not AvailablePlant Tissue Cult. & Biotech. 30(1): 161-166, 2020 (June)